How Prognostic and Predictive Biomarkers Are Transforming Our Understanding and Management of Advanced Gastric Cancer. (20th August 2014) - Kim, Christina; Mulder, Karen; Spratlin, Jennifer
Abstract : Background: Gastric cancer (GC) is the second leading cause of cancer death worldwide. GC is a heterogeneous disease in terms of histology, anatomy, and epidemiology. There is also wide variability in how GC is treated in both the resectable and unresectable settings. Identification of prognostic and predictive biomarkers is critical to help direct and tailor therapy for this deadly disease. Methods: A literature search was done using Medline and MeSH terms for GC and predictive biomarkers and prognostic biomarkers. The search was limited to human subjects and the English language. There was no limit on dates. Published data and unpublished abstracts with clinical relevance were included. Results: Many potential prognostic and predictive biomarkers have been assessed for GC, some of which are becoming practice changing. This review is focused on clinically relevant biomarkers, including EGFR, HER2, various markers of angiogenesis, proto‐oncogene MET, and the mammalian target of rapamycin. Conclusion: GC is a deadly and heterogeneous disease for which biomarkers are beginning to change our understanding of prognosis and management. The recognition of predictive biomarkers, such as HER2 and vascular endothelial growth factor, has been an exciting development in the management of GC, validating the use of targeted drugs trastuzumab and ramucirumab. MET is another potential predictive marker that may be targeted in GC with drugs such as rilotumumab, foretinib, and crizotinib. Further identification and validation of prognostic and predictive biomarkers has the potential transform how this deadly disease is managed. Abstract : Identification of prognostic and predictive biomarkers is critical to help direct and tailor therapy for gastric cancer. This review is focused on clinically relevant biomarkers, including EGFR, HER2, various markers of angiogenesis, proto‐oncogene MET, and the mammalian target of rapamycin. Further identification and validation of prognostic and predictive biomarkers has the potential transform how this deadly disease is managed.